Painful acute radiation thyroiditis induced by (131)I treatment of Graves’ disease - Shah, Kinjal K (BMJ Case Rep, 2015)
A 44-year-old woman, chronic smoker with Graves’ disease was treated with radioactive iodine ablation (RAI). One week after the treatment, she presented with severe pain in the anterior neck with radiation to the angle of the jaw associated with fatigue, tremor and odynophagia. Physical examination demonstrated an asymmetric and exquisitely tender thyroid gland. There was no laboratory evidence of thyrotoxicosis. Acute radiation thyroiditis was diagnosed. Non-steroidal anti-inflammatory drugs and hydrocodone-acetaminophen started initially were ineffective for pain control. Prednisone provided relief and was continued for 1 month with a tapering dose. Symptoms completely resolved after 1 month at which time the thyroid remained diffusely enlarged and non-tender. Three months following RAI ablation she developed hypothyroid symptoms. Levothyroxine was initiated. The patient has remained asymptomatic on continued follow-up care.